The Effectiveness of an AR Module in Enhancing Achievement and Interest in Learning Mechanical Components - Zamuri, Muhammad Firdaus; Suhaimi, Suhazlan; Hazrullah (Journal of ICT in Education, 2025)
This study explores the effectiveness of using an Augmented Reality (AR) Module on students’ achievement and interest in learning the topic of mechanical components within the Form Two Design and Technology (RBT) curriculum. Specifically, the research aimed to (i) identify the need for AR in teaching and learning, (ii) determine key mechanical components to be included in the AR module, (iii) examine the impact of the AR module on student achievement, and (iv) evaluate the relationship between AR usage and student interest. A mixed-method approach was adopted, including document analysis, teacher questionnaires, and a quasi-experimental design involving 100 Form Two students from two secondary schools in Negeri Sembilan, Malaysia. The students were divided into treatment (AR module) and control (conventional method) groups. Written tests and interest questionnaires were used as research instruments. Findings revealed that all 20 mechanical components assessed were considered suitable for inclusion in the AR module, based on high agreement levels from 17 RBT teachers (M = 4.50, SD = 0.52). The experimental data showed that students exposed to the AR Module achieved significantly higher scores (t (98) = 19.099, p < .001, η² = .788) and expressed stronger interest in the topic. A very strong positive correlation was found between achievement and interest (r = 0.973, p < .01). The results confirm that the AR module is an effective tool to enhance both academic performance and engagement in learning mechanical components, supporting the integration of AR in technical education.